Gestão de uma organização educativa: os efeitos dos processos decisórios no trabalho docente - Moreira, Viviana Pérez (Universidade do Vale do Rio dos Sinos, 2024)
This dissertation addressed the effects of management decisions on the performance of the teaching staff at an educational institution within the Jesuit Education Network (RJE) during the years 2021 to 2023. The study aimed to understand how changes in the school's management structure during this period affected the teachers' work and the pedagogical and learning processes. The research problem investigated how these changes were perceived by teachers and managers and what the implications were for teaching practices. Through a qualitative approach, involving interviews, questionnaires, and document analysis, the research sought to provide insights into the relationship between management decisions and teachers' work. In conclusion, the change in the management model revealed notable positive aspects, such as organization, communication, autonomy, and focus on professional functions. There was a favorable perception regarding the efficiency and transparency of management, as well as the new administration's ability to streamline and resolve demands more effectively and autonomously. However, there is an imperative need for school management to be sensitive to the needs of the teaching staff, to show greater presence in the teachers' daily lives, and to promote a collaborative and effective educational environment. As an intervention, it is proposed to develop a School Management Guidelines Manual as a practical initiative to provide clear guidelines and recommendations based on the conducted research.
Keywords: Gestão educacional; Corpo docente; Processos decisórios; Práticas pedagógicas; Educational management; Faculty; Decision-making processes; Pedagogical practices; ACCNPQ::Ciências Humanas::Educação